Principles of engineering thermodynamics. : SI version. - Moran Michel J., ....-; Shapiro, Howard N., ....-; Boettner Daisie D., ....-; Bailey Margaret B., ....- (Hoboken : John Wiley, 2012)
Now in a seventh edition, fundamentals of Engineering Thermodynamics continues to set the standard for teaching readers how to be effective problem solvers, emphasizing the authors' signature methodologies that have taught over a half million students worldwide.
Fundamentals of engineering thermodynamics: appendices